2023
DOI: 10.1039/d2gc04544c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically driven α-thiocarbamylation via a dehydrocoupling strategy of β-ketoesters with amines and CS2

Abstract: The development of atom- and step-economic methods for converting hazardous CS2 into harmless chemicals is a challenging endeavor. Herein, we disclose a feasible strategy for the electrochemical dehydrogenative coupling of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Mechanistically, the reaction of CS Shortly thereafter, an electrochemical protocol was developed by He and coworkers for the one-pot α-dithiocarbamation of β-keto esters and other active methylene compounds 70 with CS 2 and secondary amines 37 (Scheme 21). [114] The reactions were performed under catalyst-and oxidant-free conditions using NaO t Bu as the base and n Bu 4 NBF 4 as the electrolyte. A variety of cyclic and acyclic secondary amines including those bearing spirocyclic structures were tolerated, whereas primary amines failed to participate in the desired reactions, probably owing to the weak nucleophilicity of aromatic amines and the side reactions observed for primary aliphatic amines.…”
Section: C(sp 3 )à H Dithiocarbamationmentioning
confidence: 99%
“…Mechanistically, the reaction of CS Shortly thereafter, an electrochemical protocol was developed by He and coworkers for the one-pot α-dithiocarbamation of β-keto esters and other active methylene compounds 70 with CS 2 and secondary amines 37 (Scheme 21). [114] The reactions were performed under catalyst-and oxidant-free conditions using NaO t Bu as the base and n Bu 4 NBF 4 as the electrolyte. A variety of cyclic and acyclic secondary amines including those bearing spirocyclic structures were tolerated, whereas primary amines failed to participate in the desired reactions, probably owing to the weak nucleophilicity of aromatic amines and the side reactions observed for primary aliphatic amines.…”
Section: C(sp 3 )à H Dithiocarbamationmentioning
confidence: 99%
“…7,8 In the past few decades, the electrochemical strategy has been widely used in numerous organic research fields, such as C–H activations, 9 reductive coupling, 10 alkene difunctionalizations, 11 carboxylation reactions 12 and others. 13 Electrochemical reduction is becoming an attractive topic to fix the cost and waste problems faced in traditional chemical methods. Considering these advantages, electroreductive C–F cleavage exhibited its potential for defluorinative functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon disulfide (CS 2 ) serves as a stable and affordable C1 donor and a sulfur source. Traditionally, it functions as an electrophilic reagent, reacting with C/O/S/N-centered nucleophiles to create thiocarbonate anion compounds, facilitating coupling reactions. Contemporary research explores multistep and atom-efficient multicomponent reactions involving CS 2 , including the formation of dithiocarbamate anions and acids with amines. , Recent advancements encompass one-pot multicomponent reactions utilizing S or O-centered nucleophiles for dithiocarbamate and it’s derivatives synthesis, light-mediated diaryl dithiocarbamate formation, and electrochemical dehydro-coupling reactions producing carbonyl thiocarbamates. Pertinent to peptides, Chen et al demonstrated the CS 2 -mediated coupling of thioacids and dithiocarbamate terminal amines to construct amide bonds …”
mentioning
confidence: 99%